Between Hallyu and the Qur’an: Everyday Life of Female Santri in Yogyakarta - Nur Azka Inayatussahara; Noorhaidi Hasan (Universitas Islam Negeri Mataram, 2023)
The religious expressions of students at an Islamic boarding school, referred to as “santri,” encompassing worship, rituals, and the utilization of religious symbols or texts, unveil a captivating phenomenon showcasing the adeptness of youth in reconciling their Islamic identity with global popular culture. This paper delves into the daily lives of female santris at Pondok Pesantren Sunan Pandanaran in Sleman, Yogyakarta. It examines the creative tensions that confront these santris, who commit the Qur’an to memory while concurrently being avid enthusiasts of Korean popular culture, including K-Pop and K-Drama. For the santris who prioritize memorizing the Qur’an, they are compelled to steer clear of any elements that could impede their concentration. This holds especially true for santris who also indulge in Korean popular culture activities—actions that some deem incongruent with Islamic values. This study discerns that the santris are capable of engaging in both activities concurrently, without perceiving K-Pop as detrimental to their memorization endeavors. By assimilating practices from Korean popular culture and skillfully harmonizing them with their religious traditions, the santris occupy a distinctive position at the confluence of Islam, globalization, and youthfulness. Constituting a pivotal segment of the global populace, they strive to harmonize their religious principles with the influences of an ever-evolving world, all while preserving their youthful spirit.